Development and Maintenance of Sprint Training Adaptations: An Uphill-Downhill Study. Issue 1 (6th February 2020) - Bissas, Athanassios; Paradisis, Giorgos P.; Nicholson, Gareth; Walker, Josh; Hanley, Brian; Havenetidis, Konstantinos; Cooke, Carlton B.
Abstract: Bissas, A, Paradisis, GP, Nicholson, G, Walker, J, Hanley, B, Havenetidis, K, and Cooke, CB. Development and maintenance of sprint training adaptations: an uphill-downhill study. J Strength Cond Res 36(1): 90–98, 2022—We examined the development of performance adaptations resulting from an uphill-downhill training program and monitored the decline of adaptations during detraining. Twenty-eight men were randomly assigned to 1 of 2 sprint training groups who trained 3 times per week for 6 weeks and a control group (C). The uphill-downhill group (U+D) trained on an 80-m platform with 3° slopes, whereas the horizontal (H) group trained on flat track. Subjects were tested for maximal running speed (MRS), associated kinematics, and leg strength before and after training, with U+D subjects also tested after weeks 2 and 4 of training, and after a 3-week detraining period. The U+D group increased their MRS by 3.7% (from 8.75 ± 0.72 to 9.07 ± 0.64 m·s −1, p < 0.05), their stride rate by 3.1% (from 4.21 ± 0.21 to 4.34 ± 0.18 Hz, p < 0.05), and their knee extensors' maximum isometric force by 21% (from 2, 242 ± 489 to 2, 712 ± 498 N, p < 0.05) after training. The time course of changes showed declines for weeks 1–4 (1.4–5.1%), but an ascending trend of improvement compensated all losses by the end of week 6 ( p < 0.05). During detraining, no decreases occurred. No changes were observed for the H and C groups. The minimum period to produce positive effects was 6 weeks, with a very good standard of performance maintained 3 weeks after training. U+D training will prove useful for all athletes requiring fast adaptations, and it can fit into training mesocycles because of its low time demands.